Use of E-Commerce Platforms as Promotional Media for Daster Wear In Indonesia - Nurul Atiqah; Tila Rahmana Putri; Resky Arinata; Titin Sumarni (Penerbit Hellow Pustaka, 2024)
The development of technology has had a big influence on the world of fashion so that its circulation has encouraged sellers to be more creative in creating content that can attract buyers' interest and creating products that can meet the needs of the audience through the use of e-commerce platforms as promotional media. In this day and age, negligee clothing is considered to be clothing that most comfortable for all women, including Indonesian women. The aim and objective of this research is to find out how the e-commerce platform is used as a media for promoting negligee clothing in Indonesia. The method used in this research is a qualitative method. The researcher used the library study research method because he wanted to build a deep understanding of the research topic, identify previous research, and conduct further research related to the topic of building a make-up brand in the digital era